LA CONSOLIDACIÓN DE ESTADOS FINANCIEROS. ANÁLISIS COMPARATIVO CONTABLE MÉXICO-ESPAÑA/4. CONSOLIDATION OF FINANCIAL STATEMENTS. ACCOUNTING COMPARATIVE ANALYSIS MÉXICO – SPAIN (Revista científica Pensamiento y Gestión, 2011)
Resumen Los mecanismos de consolidación aplicables a la agrupación de empresas variarán significativamente dependiendo del formato legal empleado y del país en que se apliquen. En una fusión, donde las compañías adquiridas se disuelven legalmente, se realizará la consolidación contable una sola vez. En los casos de adquisición de acciones, en los cuales las sociedades conservarán su personalidad jurídica independiente, serán aplicables diferentes métodos de consolidación y deberá realizarse dicho proceso cada vez que se requieran estados financieros consolidados ya sea para efectos financieros o legales, debiendo conservarse independientes los registros contables de todas las sociedades integrantes.AbstractThe mechanisms of consolidation applicable to the grouping of companies will vary significantly following the used legal format and of the country in which they are applied. In a fusion, where the acquired companies dissolve legally, the countable consolidation will be realised a single time. In the cases of stocks acquisition, in which the societies will conserve their legal personality independent, they will be applicable different methods from consolidation and will have to be realised this process whenever required consolidated final statements. Those consolidated financial statements are required either for financial or legal purposes, having to conserve independent the accounting records of all the integral societies.